Implementasi User Center Design dan System Usability Scale Pada Website Sekolah Menengah Atas - Arya Sastranegara; Agung Triayudi; Nur Hayati (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
The SMA Tunas Markatin website aims to provide an effective media of information and publications for students, teachers, parents and the general public. To achieve this goal, the User-Center Design (UCD) Method and System Usability Scale (SUS) are implemented to improve user experience and user satisfaction with websites. In the UCD phase, a website-based approach. Initial user studies are conducted to understand the needs and preferences of potential users to collect data, conducted through interviews, observations, and surveys, to gain an in-depth understanding of user needs and goals. The results of this evaluation become improvements and refinement of the design. The System Usability Scale (sus) method is used to measure the level of user satisfaction with the website. Following the launch of the website, users are provided with the SUS questionnaire which consists of structured questions that measure the user's perception of the overall usability of the system. The collected data is analyzed to assess the level of user satisfaction. Based on the findings from user studies, an interactive prototype design is created and iterations are carried out involving the users. The design evaluation process involves usability testers, who provide feedback and input regarding structural information navigation, layout, and elements of the main research problems, solutions (methods) of solving problems encountered, research objectives and research temporary results which can be in the form of numbers/proportions according to research needs